Developing Teaching Factory Laboratory for Vocational Education: Case Study from Bachelor of Applied Culinary Arts - Suyono; Khamidi, Amrozi; Karwanto; Hafidz, Abdul; Sholeh, Mohamad (Proceeding of International Joint Conference on UNESA, 2025)
This study aims to develop a Teaching Factory (TEFA) laboratory framework for the Bachelor of Applied Culinary Arts program at Surabaya State University, utilizing the TF-6M Model and the ADDIE Model. The primary objective is to bridge the gap between vocational education and industry needs by creating a realistic learning environment that simulates industrial processes. The research employs a qualitative approach, involving needs analysis through interviews and surveys with industry representatives, faculty, and students. The findings indicate a significant demand for a TEFA laboratory, with 80% of respondents highlighting the necessity for practical skills training. The developed framework consists of six key steps: Receiving Orders, Analyzing Orders, Stating Readiness to Execute Orders, Executing Orders, Conducting Quality Control, and Delivering Orders. Evaluation results demonstrate high satisfaction with the teaching materials and simulations, although improvements in quality control procedures are recommended. This research contributes to enhancing students' job readiness and aligns vocational education with industry standards, showcasing the novelty of integrating practical experiences into the curriculum.